2010
DOI: 10.1007/s11079-010-9187-8
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Approach for Modelling International Trade in South-Eastern Europe and the Commonwealth of Independent States: The Role of Geography, Policy and Institutions

Abstract: The Working Paper Series of the Czech National Bank (CNB) is intended to disseminate the results of the CNB's research projects as well as the other research activities of both the staff of the CNB and collaborating outside contributor, including invited speakers. The Series aims to present original research contributions relevant to central banks. It is refereed internationally. The referee process is managed by the CNB Research Department. The working papers are circulated to stimulate discussion. The views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…Almost the same results were given by Kucharčuková, Babecký and Raiser (2010), who concluded that the poor quality of institutions in many Western Balkan countries is the major barrier to greater trade integration of this region. According to Xhelili-Krasniqi and Mustafa-Topxhiu (2017), Western Balkan countries trade more with European Union than between themselves.…”
Section: Theoretical Backgroundsupporting
confidence: 66%
“…Almost the same results were given by Kucharčuková, Babecký and Raiser (2010), who concluded that the poor quality of institutions in many Western Balkan countries is the major barrier to greater trade integration of this region. According to Xhelili-Krasniqi and Mustafa-Topxhiu (2017), Western Balkan countries trade more with European Union than between themselves.…”
Section: Theoretical Backgroundsupporting
confidence: 66%
“…In addition, a negative relationship has been revealed with the commercial sales of Kütahya between provinces and the provinces distances. In another similar study (Kucharčuková et al, 2010), it was found that the distance to the markets is less important than the quality of the institutions on the trade volume.…”
Section: Discussionmentioning
confidence: 88%
“…It was determined that China benefited from the trade agreement with the Association of Southeast Asian Nations (ASEAN) in terms of export potential and at the same time, an agreement to be made with South and East Asian countries could have great export potential. Kucharčuková et al (2010) performed a panel data analysis using the Poisson and Tobit estimation techniques with an 8-year (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) data set of 82 countries. In the study using the Gravity Model, the reason why Southeast Europe (SEE) and Commonwealth of Independent States (CIS) countries trade significantly less with the world economy than the later participating Central and Eastern European (CEE) Countries was investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The WGI measure institutional governance using 6 dimensions, namely, Voice and Accountability, Political Stability and Absence of Violence / Terrorism, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption. Studies using these data include Babecká Kucharčuková et al (2012); Gani and Prasad (2006); Iwanow and Kirkpatrick (2007); Méon and Sekkat (2008); and Soeng and Cuyvers (2018). Empirical studies utilising these data are among the most widely used, although with different variations in the use of the index between studies where some use only a few indexes.…”
Section: Graph 2 Six Dimensions Of Institutions Quality In Indonesia Source: Worldwide Governance Indicatorsmentioning
confidence: 99%